TEMPAT SAMPAH PINTAR BERBASIS ARDUINO DAN SENSOR ULTRASONIK DI SMKN 1 TIRTAJAYA - Syamtamami, Muhamad Haikal; Anas, Ahmad (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2022)
Garbage has become a part of life, we all produce waste every day, garbage can also contain many diseases and become a source of disease if left unchecked. So in this study, we will build an Arduino-based smart trash can with an ultrasonic sensor, where if we are less than 25cm away, the trash can will open automatically without us having to hold it. This study aims to reduce direct contact between humans and trash bins and hopes to reduce disease transmission, especially in the SMKN 1 Tirtajaya environment.